Periorbital oedema and surgical emphysema, an unusual complication of a dental procedure: a case report - Parkar, Asif (Cases Network Ltd, 2009)
INTRODUCTION: We report a case of subcutaneous emphysema and periorbital oedema following a dental procedure. CASE PRESENTATION: A 55-year-old female who attended Accident and Emergency department with subcutaneous emphysema of the neck and periorbital oedema several hours after having undergone root canal treatment. She was admitted for prophylactic intravenous antibiotics and was discharged the next day with oral antibiotics and recovered completely in about 10 days. CONCLUSION: Although there are existing case reports documenting the occurrence of surgical emphysema following dental procedure, there was no literature documenting a case of periorbital oedema. This can be managed with close observation and antibiotic prophylaxis as in this case but it is important that the potential seriousness of such a complications resulting from dental procedures are not overlooked.